2009
DOI: 10.1177/1545968309345268
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bilateral Arm Training on Motor Control and Functional Performance in Chronic Stroke: A Randomized Controlled Study

Abstract: Relative to CI, BAT improved the spatiotemporal control of the affected arm in both bilateral and unilateral tasks, decreased online corrections to perform bilateral tasks, and reduced motor impairment. These findings support the use of BAT to improve motor control and motor function of the affected upper limb in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 50 publications
2
99
0
6
Order By: Relevance
“…BAT, an alternative treatment approach receiving growing attention [5,21], uses the repetitive practice of symmetrical bilateral tasks to improve the motor ability of the affected limb. Numerous studies in stroke patients have shown evidence of efficacy of CIT [5,22] and BAT [5,23], but there is no consensus concerning the optimal outcome measure for assessing the health function of patients after stroke rehabilitation. There is a need for research that directly compares the responsiveness and validity of the SIS and the SS-QOL.…”
Section: Introductionmentioning
confidence: 98%
“…BAT, an alternative treatment approach receiving growing attention [5,21], uses the repetitive practice of symmetrical bilateral tasks to improve the motor ability of the affected limb. Numerous studies in stroke patients have shown evidence of efficacy of CIT [5,22] and BAT [5,23], but there is no consensus concerning the optimal outcome measure for assessing the health function of patients after stroke rehabilitation. There is a need for research that directly compares the responsiveness and validity of the SIS and the SS-QOL.…”
Section: Introductionmentioning
confidence: 98%
“…Bilateral arm training (BAT) may be of value particular for stroke patients with severe functional deficits (44). In a randomized controlled trial 6-67 months after stroke onset, BAT improved the spatiotemporal control of the affected arm in both bilateral and unilateral tasks and reduced motor impairment (45). Comparing CIMT, BAT, and a control intervention of equally intense but less specific therapy for 2 hours a day 5 days a week for 3 weeks, both CIMT and bilateral arm training resulted in better performance than the control intervention.…”
Section: Motor Rehabilitationmentioning
confidence: 99%
“…The notion of Bi‐TENS was inspired by the success of bilateral motor training,15, 16, 17, 18, 19 and positive findings26 have also been reported with bilateral leg training after stroke. In addition, training of the nonparetic limb has also been reported to enhance motor recovery in paretic limbs 15, 47…”
Section: Discussionmentioning
confidence: 99%